Peran Kepemimpinan Pendidikan Islam dalam Manajemen Perubahan Pada Lingkungan Organisasi Islam Indonesia - Fadlol, Moch. Abu; Subiyanto, Subiyanto (Idarah (Jurnal Pendidikan dan Kependidikan), 2021)
The era of disruption has an impact on the stability of educational organizations. This study aims to discuss the change management model of Islamic education institutions. The form of adaptation to global developments is to make changes at the system and governance level. This type of research is qualitative with library methods. The data is taken from research results and reference book sources that are relevant to the conception of organizational change, organizational life cycle, innovation change and organizational effectiveness. The results show the strategy of Islamic education institutions in managing change. Change occurs through three stages, the system pioneer stage, the stability stage and the competition stage. The study also found a conceptual model that was specifically described in the form of an Islamic education organizational change model, the concept of the organizational environment, the synthesis of organizational uncertainty, the concept of organizational change and change management, and the typology of Islamic organizational change.